2004
DOI: 10.1021/jm030217e
|View full text |Cite
|
Sign up to set email alerts
|

Imidazoquinoxaline Src-Family Kinase p56Lck Inhibitors:  SAR, QSAR, and the Discovery of (S)-N-(2-Chloro-6-methylphenyl)-2-(3-methyl-1-piperazinyl)imidazo- [1,5-a]pyrido[3,2-e]pyrazin-6-amine (BMS-279700) as a Potent and Orally Active Inhibitor with Excellent in Vivo Antiinflammatory Activity

Abstract: A series of novel anilino 5-azaimidazoquinoxaline analogues possessing potent in vitro activity against p56Lck and T cell proliferation have been discovered. Subsequent SAR studies led to the identification of compound 4 (BMS-279700) as an orally active lead candidate that blocks the production of proinflammatory cytokines (IL-2 and TNFalpha) in vivo. In addition, an expanded set of imidazoquinoxalines provided several descriptive QSAR models highlighting the influence of significant steric and electronic feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 68 publications
(128 reference statements)
0
18
0
Order By: Relevance
“…Incorporation of a solubilizing tether that bears a weakly basic and polar tertiary amine group to the solvent‐exposed region (the 6‐ and 7‐positions of the fused phenyl ring) of the phenyl ring of Lck inhibitor 80 (<8 μM) afforded derivatives with improved solubility (>100 μM) and superior in vitro and cellular potencies, as demonstrated by compound 81 (Figure ) …”
Section: Exploitation Of Solvent‐exposed Regions For Structure‐based mentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of a solubilizing tether that bears a weakly basic and polar tertiary amine group to the solvent‐exposed region (the 6‐ and 7‐positions of the fused phenyl ring) of the phenyl ring of Lck inhibitor 80 (<8 μM) afforded derivatives with improved solubility (>100 μM) and superior in vitro and cellular potencies, as demonstrated by compound 81 (Figure ) …”
Section: Exploitation Of Solvent‐exposed Regions For Structure‐based mentioning
confidence: 99%
“…However, proteins are quite flexible and undergo conformational changes during an induced fitting with a flexible binder. Besides, a single compound can show more than one conformation, so, based on the available three‐dimensional structures, a strategy of constraining the conformation of flexible molecules (eg, forming a macrocycle between two solvent‐exposed substituent positions of a given binder) is well‐established to improve potency, selectivity, and PKs or absorption, distribution, metabolism, and excretion (ADME)‐relatedproperties (eg, metabolic stability), while having a minimal effect on the therapeutically relevant binding interaction …”
Section: Exploitation Of Solvent‐exposed Regions For Structure‐based mentioning
confidence: 99%
“…On the basis of the experimental data from various studies [23][24][25], chemists have found quinoxaline motifs to be highly expeditious building blocks in medicinal research. This is due to wide biological properties they possess.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…Quinoxaline motif is known to represent a class of medicinally important compounds which are effective as antibacterial [1,4], antifungal [2,10], anticancer [11], analgesic [12], antimalarial [13], antitumor [14], antiamoebic [15], antiepileptic [16], anticonvulsant [17], antitubercular [18], antiproliferative [19], anti-HCV [20], anti-inflammatory [21] agents among others. Compounds with quinoxaline cores are used as allosteric dual Akt1 and Akt2 inhibitors, human cytomegalovirus polymerase inhibitors [22], Src-Family Kinase p56Lck inhibitors [23], SRPK-1 inhibitors [24] and monoamine oxidase A inhibitors [25]. Report has shown recently that pyrrolo[1,2-a]quinoxaline derivatives are potent and selective 5-HT 3 ligands [12].…”
Section: Introductionmentioning
confidence: 99%
“…The successes and problems of these inhibitors have raised significant interest and efforts in discovering new Src inhibitors [5-7]. Several in-silico methods have been used for facilitating the search and design of Src inhibitors, which include pharmacophore [8], Quantitative Structure Activity Relationship (QSAR) [9], and molecular docking [6]. …”
Section: Introductionmentioning
confidence: 99%